Synthetic polymers enable non-vitreous cellular cryopreservation by reducing ice crystal growth during thawing. - Deller, R; Vatish, M; Mitchell, D; Gibson, M (Nature Publishing Group, 2014)
The cryopreservation of cells, tissue and organs is fundamental to modern biotechnology, transplantation medicine and chemical biology. The current state-of-the-art method of cryopreservation is the addition of large amounts of organic solvents such as glycerol or dimethyl sulfoxide, to promote vitrification and prevent ice formation. Here we employ a synthetic, biomimetic, polymer, which is capable of slowing the growth of ice crystals in a manner similar to antifreeze (glyco)proteins to enhance the cryopreservation of sheep and human red blood cells. We find that only 0.1 wt% of the polymer is required to attain significant cell recovery post freezing, compared with over 20 wt% required for solvent-based strategies. These results demonstrate that synthetic antifreeze (glyco)protein mimics could have a crucial role in modern regenerative medicine to improve the storage and distribution of biological material for transplantation.